2016
DOI: 10.1016/j.ejmech.2016.05.026
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant-like effects and mechanisms of flavonoids and related analogues

Abstract: Flavonoids, possessing a basic phenylbenzopyrone core, are important components of the human diet, and are found in many medicinal plants. Flavonoids include chalcones, flavanones and their derivatives. Synthetic and natural isolated flavonoids display an enormous number of biological activities such as antitumor, antiplatelet, anti-malarial, anti-inflammatory, antidepressant and anticonvulsant properties. This review article focuses on the antidepressant-like effect, structure-activity relationship and mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
76
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(77 citation statements)
references
References 92 publications
1
76
0
Order By: Relevance
“…Noteworthy, the antidepressant-like activity has been demonstrated for rosmarinic acid (32), luteolin (33), rutin (34,35) and catechin (36). Moreover, previous studies have shown that tannins and flavonoids can possess antide-pressant effects (37,38). In this regard, it is notable that the antidepressant activity of S. elegans has been attributed to a flavon, named isosakuranetin-5-O-rutinoside (39).…”
Section: Discussionmentioning
confidence: 99%
“…Noteworthy, the antidepressant-like activity has been demonstrated for rosmarinic acid (32), luteolin (33), rutin (34,35) and catechin (36). Moreover, previous studies have shown that tannins and flavonoids can possess antide-pressant effects (37,38). In this regard, it is notable that the antidepressant activity of S. elegans has been attributed to a flavon, named isosakuranetin-5-O-rutinoside (39).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies by Freitas et al in 2014 and Mai et al in 2015 reported that many flavonoids possess antioxidant, antiinflammatory, and antidepressant activities in animal studies [27,28]. The monoamine theory of depression indicates that, the main biochemical causes of depression are metabolic disorders of monoamine neurotransmitters that are involved in NE, 5-HT, and DA signaling [29,30]. Thus, the anxiolytic-antidepressant effects of O. barrelieri, could involve mechanisms both dependent and independent of the neurogenesis process in many brain areas by setting of a new physiological state, which would probably facilitate an increase of monoamines (serotonin) action [31; 32].…”
Section: Discussionmentioning
confidence: 98%
“…Some studies have reported antidepressant effect of some flavonoids and flavonoids containing plant extracts [54]- [55]. For instance, Hypericum perforatum is a strong antidepressant of plant origin; its antiimmobility effect has been attributed to the presence of rutin and quercetin [54][55][56]. More also, Ginkgo biloba L. (Ginkoaceae) leaf extract has demonstrated antiimmobility effect in despair swim test [57].…”
Section: Discussionmentioning
confidence: 99%